Anti-glomerular basement membrane (anti-GBM) disease: the challenges in diagnosis and the choice of treatment - Li, Li Kwan; Lim, Christopher Thiam Seong; Yong, Fatt Cheng; Abd Ghani, Fauzah; Ramli, Raihan (Malaysian Society of Nephrology, 2024)
Anti–glomerular basement membrane (anti-GBM) antibody disease is an autoimmune disorder. The majority of patients develop widespread glomerular crescent formation, presenting with features of rapidly progressive glomerulonephritis (RPGN). The etiology is unclear. The treatment depends on the creatinine level at presentation, dialysis dependency, and pulmonary involvement to decide on plasmapheresis, glucocorticoid, and immunosuppressive therapy. We report a case of a 17-year-old lady who presented features of RPGN requiring intermittent dialysis, renal biopsy, and serology showing features of anti-GBM glomerulonephritis (GN).